PTH-132 Medical Students' Perception of Nutrition Education at An Undergraduate Level and The Role of The Clinicians They Shadow. (17th August 2016) - Neild, P; Long, W
Abstract : Introduction: Medical schools have neglected nutrition training in undergraduate courses, resulting in medical students being unsure of its importance 1 and doctors not confident in managing nutrition-related problems. 2 The aim of this study was to explore medical students' views and experiences of nutrition training at different stages of their training and to evaluate the impact of the views of the clinicians they shadowed. Methods: A cross-sectional email survey of all medical students in the first (T) and final (F) clinical years at St. George's University of London was conducted. Clinicians at St. George's hospital were surveyed with a 10 item questionnaire. Data were analysed using SPSS version 21.0 and the significance determined using a 2 tailed Fischer's exact test. Results: The overall student response rate was 106/549 (19.3%) with no significant difference between the 2 year groups. 86/ 500 clinicians responded. 75% of students agreed that 'having a strong understanding of nutrition is an important aspect of a doctor's job'. Of those that disagreed, 57% cited as a reason that 'other members of the healthcare team deal with nutrition problems'. 71% of students agreed that 'nutrition should be included in the undergraduate medical curriculum'. The only students to disagree were from F year (12% vs 0%, p = 0.016) and 36% of them cited as a reason that their 'medical school timetable is too full'. Only 11% of students had had the importance of nutrition highlighted to them by a senior clinician 'regularly'. This group were more likely to 'strongly agree' with the statements above than those who had not (24% vs 3%, P = 0.02 and 21% vs 6%, P = 0.039). However, only 17% of clinicians frequently emphasised the importance of nutrition problems and only 7% frequently emphasised the importance of nutrition screening tools to students. The most commonly cited reason for clinicians not emphasising these was 'it does not occur to me' Only 50% of clinicians said they were confident managing nutrition related problems and for the majority (63.4%) of confident clinicians, it took greater than one year as a doctor to achieve this confidence. Conclusion: It appears that whilst senior clinicians do have an impact on how students perceive the importance of nutrition, they do not emphasise it enough and; this may be due to themselves viewing it as a low priority or a lack of confidence. The greater likelihood of F year students disagreeing with nutrition's inclusion in the curriculum may result from increased time spent on clinical placements compared with T year students, allowing their perception of nutrition to be negatively influenced by the clinicians they shadowed. References: 1 Tripisciano F, Neild P. Proceedings of the Nutrition Society . 2010;69 (0CE2). 2 Nightingale JM, et al . Clin Nutr . 1999;18 (1):23–27. Disclosure of Interest: None Declared